Socio-cultural conditions of victims and their crime reporting practices in Lagos, Nigeria - Ayodele, Johnson Oluwole (African journal of criminology and justice studies, 2016)
Socio-cultural conditions of victims are critical components for effective policing of traditional neighborhoods. Nevertheless, little research attention has been paid to how these conditions drive victims’ reporting decision-making. This study examines the influence of socio-cultural conditions on reporting among victims in Lagos, Nigeria, using quantitative and qualitative methods. Multistage sampling consisting of purposive and simple random techniques was used to select study locations and respondents respectively. Quantitative data were analyzed at three levels. Qualitative data were content analyzed. Logistic regression results indicated that respondents, who reported that extended family connections frustrate crime reporting, are eight times more likely to discourage crime reporting relative to other factors. Moreover, respondents who reported that cooperation, which the extended family connections provide sometimes conceal crime, is over two times more likely to discourage crime reporting relative to other factors. The study concludes that socio-cultural conditions are significant correlates of reporting. It suggests that government should make community norms drive reporting to restore hope for justice and build less violent communities in Lagos.